2022
DOI: 10.3389/fpls.2021.804315
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Heat Tolerant Cotton Lines Showing Genetic Variation in Cell Membrane Thermostability, Stomata, and Trichome Size and Its Effect on Yield and Fiber Quality Traits

Abstract: Heat stress in cotton reduces its productivity. The development of heat-tolerant cotton varieties having resilience against changing climate is feasible. The purpose of this study was to probe the genetic variability in upland cotton for heat tolerance, the association of cell membrane thermostability (CMT), stomata, and trichome size with cotton adaptation to high temperature and effective breeding strategy to advance the valued traits. Relative cell injury percentage (RCI%) in studied genotypes ranged from 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…A research on cotton ( Gossypium barbadense L.) found that a combination of drought and high temperatures had a negative impact on physiological processes such as development and advancement if compared to a single stress [ 24 , 4 ]. Cotton breeding initiatives should concentrate on selecting during combined drought and heat tolerance rather than just one of these conditions [ 25 ].The main objectives of this review are to focus on the environmental factors, such as temperature, heat and drought, influences the growth and development, morphology and physio-chemical alteration of cotton. Furthermore, recent advancement on cotton breeding to combat the serious threat of drought and heat.…”
Section: Cotton Under Heat Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…A research on cotton ( Gossypium barbadense L.) found that a combination of drought and high temperatures had a negative impact on physiological processes such as development and advancement if compared to a single stress [ 24 , 4 ]. Cotton breeding initiatives should concentrate on selecting during combined drought and heat tolerance rather than just one of these conditions [ 25 ].The main objectives of this review are to focus on the environmental factors, such as temperature, heat and drought, influences the growth and development, morphology and physio-chemical alteration of cotton. Furthermore, recent advancement on cotton breeding to combat the serious threat of drought and heat.…”
Section: Cotton Under Heat Stressmentioning
confidence: 99%
“…However, as the daytime temperature rises above 30 °C, severe heat stress throughout blooming results in the loss of leaves and blooms. A rise in fruit production sites of 50% is observed as a result of temperature increases of 10 °C, or from 30 to 40 °C [ 25 ]. According to reports, freshly developed bolls begin to shed when the daytime average temperature is 32 °C or even higher.…”
Section: Influence Of Heat Stress On Morphological Traits Of Cottonmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, previous studies have identified heat‐resistant cotton by measuring changes in field agronomic traits and physiological indexes under HT. These include fruit branch height (Singh et al., 2007), number of buds per plant (Saleem et al., 2018), pollen germination rate (Huang et al., 2022), pollen tube length (Kakani et al., 2005), boll shedding rate and sterile seed rate (Demirel et al., 2016), boll weight, boll number (Kakani et al., 2005), stomatal conductivity (Abro et al., 2022), chlorophyll content (Singh et al., 2007) and cell membrane thermal stability (Kakani et al., 2005; Malik et al., 1999; Rahman et al., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of molecular biology, it has enabled people to understand the mechanism of plant resistance to stress at the molecular level of genetic composition, expression regulation, and signal transduction, especially in the molecular response of plants caused by abiotic stress. They will have severe impacts throughout the cotton growth and development stage, including a range of changes in plant morphology, physiology, quality and yield ( Pei et al, 2020 ; Abro et al, 2022 ). Therefore, studying the adaptability of cotton to abiotic adversity and cultivating new varieties of resistant cotton are of great practical significance for cotton production.…”
Section: Introductionmentioning
confidence: 99%